The role of Mycobacterium tuberculosis Rv3166c protein-derived high-activity binding peptides in inhibiting invasion of human cell lines (2012)
Given the urgent need for designing a new antituberculosis vaccine conferring total protection on patients of all ages, following the line of research adopted by our institute, this work has identified Mycobacterium tuberculosis (Mtb) Rv3166c protein high-activity binding peptides (HABPs) which are able to inhibit bacterial invasion of U937 (monocyte-derived macrophages) and A549 (type II alveolar epithelial cells) cell lines. The presence and transcription of the rv3166c gene in the Mtb species complex was confirmed by polymerase chain reaction (PCR) and reverse transcriptase-PCR; Rv3166c expression was evaluated by western blot and cellular localisation confirmed by immunoelectron microscopy. Its presence was mainly determined on cell surface. Sixteen peptides covering its entire length were chemically synthesised and tested for their ability to bind to U937 and A549 cells. Two U937 HABPs were identified and three for A549, one of them being shared by both cell lines. The four HABPs found inhibited Mtb entry by 15.0794.06. These results led us to including Rv3166c HABPs as candidates for further studies contributing towards the search for a multiepitope, chemically synthesised, subunit-based antituberculosis vaccine. © 2012 The Author.